The relative controls on forest fires and fuel source fluctuations in the Holocene deciduous forests of southern Wisconsin, USA - Mueller, Joshua Robert (Kansas State University, 2013)
Reconstructing fire regimes and fuel characteristics is an important aspect of understanding past forest ecosystem processes. Fuel sources and disturbance regimes throughout the upper Midwestern United States have been shown to be sensitive to regional climatic variability such as drought periods on millennial timescales. Yet, records documenting the complex connections between disturbance activity and the corresponding fuel source fluctuations in mesic deciduous forests and oak savanna forests in this region are limited. Thus, it has been difficult to provide a framework to evaluate drought conditions on fire activity and the relationships with fuel source fluctuations in this region. Here, I conducted high-resolution charcoal analyses of lake sediments from four sites in southeastern-southcentral Wisconsin (USA) to characterize fire activity and fuel source fluctuation in mesic deciduous forests and prairie-oak savanna over the last 10,000 years. I found that fire regimes across the four study sites have been asynchronous throughout the Holocene, due to site-specific differences that have strongly influenced local fire regimes. I also found that during periods of high fire activity the primary fuels were from arboreal sources, and during periods of low fire activity the primary fuels were from non-arboreal sources. However, fluctuations in fuel sources did not always correspond to changes in vegetation, or changes in fire frequency.
Keywords: Fire; Vegetation; Fuels; Moisture; Drought; Biology (0306); Forestry (0478); Geography (0366)